Dwight D. Eisenhower papers - Eisenhower, Dwight D. (Dwight David), 1890-1969.
Copy of Eisenhower's appointment as general of the army (1944), copy of proclamations of military rule in Austria and Germany made by Eisenhower as supreme commander of Allied Forces (1945), annotated typescript of "Summary of Operations in Northwest Europe" (1946), letter to William E. Brooks concerning Brooks's book on Ulysses S. Grant, copy of inaugural address and prayer (1953), draft copy of speech on disarmament given in Geneva, Switzerland (1955), and a program for a memorial service honoring Eisenhower (1969).
In part, photocopies.
U.S. President, president of Columbia University, and army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brooks, William E. -- 1875-1960 -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Inauguration, 1953.; Grant, Ulysses S. -- 1822-1885.; Allied Forces; World War, 1939-1945 -- Europe; Disarmament; Army officers; College presidents; Presidents -- United States